Vital Capacity and its Relation to Height and Weight - Nataraja NP; Rashmi Mohanraj (Journal of All India Institute of Speech and Hearing, 1970)
The  study  was  conducted to  find  out  the possibilities of predicting  the vital  capacity based on  height  and  weight  of an  individual.  In 15  male and 15 female  adults the height,  weight and vital capacity  were measured and nomograms were developed. In another 15 male and 15 female adults the height and weight were measured and the  vital capacity for each  indi- vidual was  predicted using  previously  developed   nomograms. Then the vital capacity was measured in  these  subjects  using an expirograph. The predicted and  obtained  vital  capacities  were found to be  within  1 +  300 c.c for  all the  subjects. Thus  it  was  found that  it  would be possible  to predict  vital  capacity  based  on height and weight.